X-ray radiation and runaway electron beams generated during discharges in atmospheric-pressure air at rise times of voltage pulse of 500 and 50 ns. (26th June 2018) - Sorokin, D.A.; Tarasenko, V.F.; Zhang, Cheng; Kostyrya, I.D.; Qiu, Jintao; Yan, Ping; Baksht, E.Kh.; Shao, Tao
Abstract: The parameters of X-ray radiation and runaway electron beams (RAEBs) generated at long-pulse discharges in atmospheric-pressure air were investigated. In the experiments, high-voltage pulses with the rise times of 500 and 50 ns were applied to an interelectrode gap. The gap geometry provided non-uniform distribution of the electric field strength. It was founded that at the voltage pulse rise time of 500 ns and the maximum breakdown voltage U m for 1 cm-length gap, a duration [full width at half maximum (FWHM)] of a RAEB current pulse shrinks to 0.1 ns. A decrease in the breakdown voltage under conditions of a diffuse discharge leads to an increase in the FWHM duration of the electron beam current pulse up to several nanoseconds. It was shown that when the rise time of the voltage pulse is of 500 ns and the diffuse discharge occurs in the gap, the FWHM duration of the X-ray radiation pulse can reach ≈100 ns. It was established that at a pulse-periodic diffuse discharge fed by high-voltage pulses with the rise time of 50 ns, an energy of X-ray quanta and their number increase with increasing breakdown voltage. Wherein the parameter U m / pd is saved.